Infrastructure Requirements For A UNESCO World Heritage Archival (short paper) - Champion, Erik (2015)
A group of academics and partners are proposing to UNESCO to run a project to survey, collate and develop tools for heritage sites and related built environments, focusing initially on Australia. We intend to consolidate and disseminate 3D models and virtual environments of world heritage sites, and host virtual heritage examples, tutorials, tools and technologies so heritage groups and classrooms can learn how to develop and maintain 3D models and virtual environments. The primary aim is to help educate the public in the area of world heritage sites via interactive digital media, with an emphasis on providing training resources for free and open source software. We will also integrate and extend existing and new infrastructure to support this learning material and the integration of scholarly publications, publicly available media and online directories and repositories of digital 3D models of world heritage sites and related artefacts.